De-risking rice-based production systems in the Philippines - Mary Anne R. Gutierrez; Jeny Raviz; Rowena Castillo; Jane Girly Balanza; Cornelia Garcia; Marie Aislinn Cabriole; Julian Gonsalves; Emily Monville-Oro; Alice Laborte; Jon Hellin (2023)
Smallholder farmers are among the most vulnerable groups affected by climate-related risks such as drought, flooding and high temperatures. With anticipated increase in frequency and severity of these risks, poor yield and crop failure will further threaten smallholder farmers’ livelihood. The CGIAR initiative on Climate Resilience (ClimBeR) aims to transform the climate adaptation capacity and increase the resilience of smallholder production systems to withstand severe climate change effects in six countries including the Philippines.